Homens e mulheres de Riba Mar: a pesca artesanal de Porto Inglês, Cabo Verde, em perspectiva etnográfica - Joao Paulo Araujo Silva (2018)
Through fieldwork in Porto Inglês, an island of Maio, in the archipelago of Cape Verde, I came across a fracture in the narrative of artisanal fishermen about their craft. This narrative divides the lived time between a past of abundance and a future of anguish, which is indicative of the current situation of overexploitation of traditional fishing areas triggered by industrial catches. Based on the narratives of the artisanal fishermen and fishmongers about their craft, this dissertation seeks to discuss the historical reasons of social marginality of these agents in the Cape Verde context, as well as intends to identify links between this process and the absence of political representation of these subjects in the scope of discussions about fish shortage.